Fixation of Ethylenediamine Using Magnesium Tetraphenylporphyrin for CO2 Capture - Gao1, Fei; Zhang1, Jianbin; Huang1, Huijuan; Wen2, Yi; Huo1, Tianrui (Asian Journal of Chemistry, 2013)
Supramolecular recognition of magnesium tetraphenylporphyrin (MgTPP) with ethylenediamine for CO2 capture was investigated in CH2Cl2 by steady-state fluorescence and UV-visible absorption spectroscopic techniques. The UV-visible spectra showed that interaction of MgTPP with ethylenediamine resulted in red shift of 2 nm for MgTPP Soret band. Once introduced, CO2 competes with MgTPP for ethylenediamine, which eventually leads to the release of MgTPP. The fluorescence spectra suggested that MgTPP interacted with ethylenediamine to form 1: 1 molecular adducts. The binding of MgTPP with ethylenediamine with the association constants (Kassoc) of (3.901 to 4.122) is not only endothermic but entropy-driven with DH = 4.402 kJ mol-1, DS = 25.980 J mol-1 K-1 and DG = -3.374 kJ mol-1 at T = 298.15 K.